2022
DOI: 10.3389/fcvm.2022.1041044
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dorzagliatin for type 2 diabetes mellitus: A meta-analysis and trial sequential analysis

Abstract: ObjectiveTo evaluate the efficacy and safety of dorzagliatin in the treatment of type 2 diabetes mellitus (T2DM) by using meta-analysis and trial sequential analysis (TSA).MethodSearch for clinical trials of dorzagliatin for T2DM in eight databases, with a time limit of build to July 2022. The included studies that met the requirements were carried out for meta-analysis and TSA.ResultsIn terms of efficacy endpoints, meta-analysis showed that dorzagliatin decreased glycated hemoglobin A1c(HbA1c) [mean differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…A meta-analysis and trial sequential analysis (TSA) incorporating three clinical studies—phase II, phase III (SEED and DAWN trials)—confirmed the benefits of dorzagliatin in lowering HbA1c, FPG, and 2h-PPG. Additionally, TSA affirmed an increase in HOMA2-b and a decrease in HOMA2-IR [ 69 ]. Results from these trials suggest that dorzagliatin can be administered to patients with mild-to-moderate diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis and trial sequential analysis (TSA) incorporating three clinical studies—phase II, phase III (SEED and DAWN trials)—confirmed the benefits of dorzagliatin in lowering HbA1c, FPG, and 2h-PPG. Additionally, TSA affirmed an increase in HOMA2-b and a decrease in HOMA2-IR [ 69 ]. Results from these trials suggest that dorzagliatin can be administered to patients with mild-to-moderate diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of safety, despite an overall higher incidence of total AEs in individuals treated with the dual agonist GKA, both the meta-analysis and TSA confirmed that dorzagliatin does not elevate serious AEs. The observed adverse reactions might be attributed to a combination of single AEs and intrinsic individual characteristics, thereby justifying its favorable safety profile [ 69 ]. A notable advantage of dorzagliatin is its safety in controlling hyperglycemia in patients with DKD or renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The subject words covered the terms “ZYC” and “CHF.” The free words were expanded to complete the search in conjunction with the subject words. [18,19]…”
Section: Methodsmentioning
confidence: 99%
“…The English subject terms cover “Fufang Xueshuantong” and “glaucoma,” and the Chinese subject terms cover “Fufang Xueshuantong Jiaonang” and “Qingguangyan.” On the basis of the subject terms, the Chinese free words are expanded by China Biology Medicine and the English free words are expanded by MeSH database, and then the subject terms and free words were combined for searching. [ 11 ]…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the subject terms, the Chinese free words are expanded by China Biology Medicine and the English free words are expanded by MeSH database, and then the subject terms and free words were combined for searching. [11]…”
Section: Literature Searchmentioning
confidence: 99%